Peran Guru Pendidikan Jasmani terhadap Kebugaran Jasmani Siswa: Studi Kasus di Indonesia dan Malaysia - cepi, Muhammad Cepi Arif Mulyana; Akbar, Maulana; Angga Permadi, Asep; Fadila Kasim, Nor; Afiq ikhmal, Muhammad (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The purpose of this article was to find out the role of physical education teachers in Indonesia and Malaysia where the role is regulated in the curriculum that has been compiled by the government. Materials and Methods. The method used in this study was a literature review study, the theoretical sources of which were obtained through analysis of the research literature that was used as a reference in the preparation of the article. This reference-based study did not involve fieldwork or direct interaction with respondents, but the data needed was obtained from various sources such as books, journals, and articles that were relevant to the theme and purpose of the article. The data was then analyzed to obtain results in the writing of the article in the form of reviewed information and accurate data. Results. The role of physical education teachers is very important in improving students' physical fitness between the role of teachers in Indonesia and Malaysia. The role of physical education teachers is responsible for guide, teaching, and providing motivation or encouragement to students to be active in physical activities or activities, which ultimately provide something that has a positive impact on the health and physical fitness of students. Conclusions. Indonesia uses the Independent Curriculum while Malaysia uses the Sekolah Standard Rendah Curriculum while the learning approach is the same, the ultimate goal is to encourage students to lead active lifestyles and support their physical and mental health.